Effects of silver nanoparticles on radish sprouts: Root growth reduction and modifications in the nutritional value - Nubia eZuverza-Mena; Raul eArmendariz Jr.; Jose R Peralta-Videa; Jorge L Gardea-Torresdey (Frontiers in Plant Science, 2016)
Reports indicate that silver nanoparticles (nAg) are toxic to vegetation, but little is known about their effects in crop plants. This study examines the impacts of nAg on the physiology and nutritional quality of radish (Raphanus sativus) sprouts. Seeds were germinated and grown for five days in nAg suspensions at 0, 125, 250, and 500 mg/L. Seed germination and seedling growth were evaluated with traditional methodologies; the uptake of Ag and nutrients was quantified by inductively coupled plasma-optical emission spectroscopy (ICP-OES) and changes in macromolecules were analyzed by infrared (IR) spectroscopy. None of the nAg concentrations reduced seed germination. However, the water content (% of the total weight) was reduced by 1.62%, 1.65%, and 2.54% with exposure to 125, 250 and 500 mg/L, respectively, compared with the control. At 500 mg/L, the root and shoot lengths were reduced by 47.7% and 40%, with respect to the control. The seedlings exposed to 500 mg/L had 901±150 mg Ag/kg dry wt and significantly less Ca, Mg, B, Cu, Mn, and Zn, compared with the control. The infrared spectroscopy analysis showed changes in the bands corresponding to lipids (3000 – 2800 cm-1), proteins (1550 - 1530), and structural components of plant cells such as lignin, pectin and cellulose. These results suggest that nAg could significantly affect the growth, nutrient content and macromolecule conformation in radish sprouts, with unknown consequences for human health.